Islam, Pendidikan dan Perempuan - Ainurrafiq, Ainurrafiq (Musawa Jurnal Studi Gender dan Islam, 2008)
The most important woman's right according to Islam is the right for education. The history shows that Islam came to deconstruct the culture of Dark Age society: the culture that discriminated women and did not take into account the rights of women including women's educational right. Islam, then, gives women and men the same dignity and access to knowledge. The dignity in Islam is not determined by one's prosperity, physical measurement, or public recognition. It is determined solely by one's piety. In the context of Indonesia, R.A. Kartini's assertion concerning the urgency of education for women is valuable. She affirms: "the intelligence of people in this country (Indonesia) will not be significantly increasing if women are left behind: women are the caregivers of civilization, How could women as the mother of this country educate the children if they are not uneducated?"